1998
DOI: 10.1128/jvi.72.4.2733-2737.1998
|View full text |Cite
|
Sign up to set email alerts
|

Immature Dendritic Cells Selectively Replicate Macrophagetropic (M-Tropic) Human Immunodeficiency Virus Type 1, while Mature Cells Efficiently Transmit both M- and T-Tropic Virus to T Cells

Abstract: Dendritic cells (DCs) can develop from CD14+ peripheral blood monocytes cultured in granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin 4 (IL-4). By 6 days in culture, the cells have the characteristics of immature DCs and can be further induced to mature by inflammatory stimuli or by monocyte-conditioned medium. After infection with macrophagetropic (M-tropic) human immunodeficiency virus type 1 (HIV-1), monocytes and mature DCs show a block in reverse transcription and only form early t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
107
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(124 citation statements)
references
References 29 publications
15
107
1
1
Order By: Relevance
“…Recent studies suggest that feline dendritic cells (feDC) play a role in the transmission of FIV comparable to that of human DC and HIV infection. It was shown in vitro that feDC can increase FIV infection of resting cells, but in particular of activated CD4 + Tcells [114,115], which is reminiscent of in vivo results obtained for HIV and SIV [89,116,117]. Early studies showed that FIV can interact with C-type lectin receptors, like human DC-SIGN, and that this interaction facilitated FIV infection in trans [118], similar to the mechanism described for HIV-1 (see above).…”
Section: Fiv Vaccine Candidatesmentioning
confidence: 58%
See 1 more Smart Citation
“…Recent studies suggest that feline dendritic cells (feDC) play a role in the transmission of FIV comparable to that of human DC and HIV infection. It was shown in vitro that feDC can increase FIV infection of resting cells, but in particular of activated CD4 + Tcells [114,115], which is reminiscent of in vivo results obtained for HIV and SIV [89,116,117]. Early studies showed that FIV can interact with C-type lectin receptors, like human DC-SIGN, and that this interaction facilitated FIV infection in trans [118], similar to the mechanism described for HIV-1 (see above).…”
Section: Fiv Vaccine Candidatesmentioning
confidence: 58%
“…More interestingly, infection may also occur in trans, when the DC delivers the infectious particle to T-cells that interact with the DC [84,86]. In this regard, mature DC has been shown to increase transmission of both R5 and X4 viruses to T-cells [87][88][89][90]. The precise involvement of DC-SIGN in this process is still unclear [91].…”
Section: Enhancement Of Hiv Replication After Activation Of Cell-medimentioning
confidence: 99%
“…In vitro, different sources of DCs and LCs have been used to detect infection with HIV. These include LCs from skin [17][18][19][20] and vagina [21], different subsets of DCs in blood [22][23][24], and DCs generated in large numbers from monocytes [25][26][27][28] or from CD34 + progenitors [29]. In each case it is possible to demonstrate infection of some DCs, but again the frequency is low, particularly relative to cultures of CD4 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Only several percent or less of the DCs in the cultures express detectable levels of newly synthesized viral protein (e.g. HIV gag p24), and immature forms of DCs are more susceptible to productive infection [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation